Extraction, Characterization and Epoxidation of Cotton Seed Oil - Abdullahi Muhammad; Fai Frederick; Chiroma Muhammad (Nanochemistry Research)
Epoxidized vegetable oils are promising candidates as raw material substitutes for industrial applications. The Chemical modification of epoxies appears to be a pathway towards achieving this goal of replacing raw materials with industrial products. In this study, oil was extracted from cottonseed using a Soxhlet extractor, yielding 35% cottonseed oil. The results obtained in the cottonseed oil characterization were determined as follows: an iodine value of 114.7gI2/100g, acid value of 0.66mgKOH/g, saponification value of 191.2mgKOH/g, specific gravity of 0.923g, peroxide value of 10.42mEq/kg, pH 4.1. The oil was epoxidized using 30% aqueous hydrogen peroxide as the oxygen donor and glacial acetic acid as the oxygen carrier in the presence of sulphuric acid as catalyst. The fresh oil and the products of the epoxidation reaction were characterized using FTIR analysis, the results of which indicated the disappearance of the carbon-carbon double bond peak at 1655 cm-1 and the appearance of the epoxide peak at 785 cm-1. The analysis also showed the strength of the synthetic epoxy, cotton epoxy cured in 21 minutes versus commercial epoxy cured in 8 minutes. Vegetable oils that have undergone epoxidation are interesting alternatives to replace raw materials in industrial applications. Epoxies can potentially be chemically altered in order to replace raw materials with industrial goods. The following conclusions were drawn from the cottonseed oil characterisation results: the specific gravity is 0.923g, peroxide content is 10.42mEq/kg, pH is 4.1, iodine value is 114.7gI2/100g, acid value is 0.66mgKOH/g, and saponification value is 191.2mgKOH/g. FTIR analysis was employed to characterize the fresh oil and the epoxidation reaction's products.